House Calls for Seniors: Building and Sustaining a Model of Care for Homebound Seniors - Beck, Robin A. (2009)
Homebound seniors suffer from high levels of functional impairment and are high-cost users of acute medical services. This article describes a 7-year experience in building and sustaining a physician home visit program. The House Calls for Seniors program was established in 1999. The team includes a geriatrician, geriatrics nurse practitioner, and social worker. The program hosts trainees from multiple disciplines. The team provides care to 245 patients annually. In 2006, the healthcare system (62%), provider billing (36%), and philanthropy (2%) financed the annual program budget of $355,390. Over 7 years, the team has enrolled 468 older adults; the mean age was 80, 78% were women, and 64% were African American. One-third lived alone, and 39% were receiving Medicaid. Reflecting the disability of this cohort, 98% had impairment in at least one instrumental activity of daily living (mean 5.2), 71% had impairment in at least one activity of daily living (mean 2.6), 53% had a Mini-Mental State Examination score of 23 or less, 43% were receiving services from a home care agency, and 69% had at least one new geriatric syndrome diagnosed by the program. In the year after intake into the program, patients had an average of nine home visits; 21% were hospitalized, and 59% were seen in the emergency department. Consistent with the program goals, primary care, specialty care, and emergency department visits declined in the year after enrollment, whereas access and quality-of-care targets improved. An academic physician house calls program in partnership with a healthcare system can improve access to care for homebound frail older adults, improve quality of care and patient satisfaction, and provide a positive learning experience for trainees.